Semillero de investigación en calidad ambiental como propuesta de innovación en el proceso de investigación formativa - Beltrán, Héctor E. (Revista Científica, 2011)
Through this research project, activities tending to the develop competences that tought to form the biology ́s teacher for the future have been developed. The activities carried out were lectures, seminaries, whose main purpose was set the theoretical foundations on several topics of environmental education, environmental quality and biology teaching, supported on literature on the subject. Lab and field activities, were made in order to relate theoretical with practical aspects. The personal work wich represents the student ́s contribution as far as the accomplishment of the planned activities of the research seedbed.